2008
DOI: 10.1158/0008-5472.can-07-6790
|View full text |Cite
|
Sign up to set email alerts
|

Transporter-Mediated Protection against Thiopurine-Induced Hematopoietic Toxicity

Abstract: Thiopurines are effective immunosuppressants and anticancer agents, but intracellular accumulation of their active metabolites (6-thioguanine nucleotides, 6-TGNs) causes dose-limiting hematopoietic toxicity. Thiopurine S-methyltransferase (TPMT) deficiency is known to exacerbate thiopurine toxicity. However, many patients are highly sensitive to thiopurines for unknown reasons. We show that Mrp4 is abundant in myeloid progenitors and tested the role of the multidrug-resistance protein 4 (Mrp4), an ATP binding … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 22 publications
6
130
1
Order By: Relevance
“…Of note, in our previous experience (unpublished), such systemic effects on any of these systems were not observed when sulforaphane, another potent Nrf2 activator, was topically administered under similar experimental conditions. MRP4 participates in the export of nucleoside monophosphate analogs (41)(42)(43), and its inducible gene expression is known to be regulated by Nrf2 (40,44,45). Furthermore, silencing of mrp4 increases the 6-TG incorporation in DNA of Hepa1c1c7 cells treated with this thiopurine (36).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, in our previous experience (unpublished), such systemic effects on any of these systems were not observed when sulforaphane, another potent Nrf2 activator, was topically administered under similar experimental conditions. MRP4 participates in the export of nucleoside monophosphate analogs (41)(42)(43), and its inducible gene expression is known to be regulated by Nrf2 (40,44,45). Furthermore, silencing of mrp4 increases the 6-TG incorporation in DNA of Hepa1c1c7 cells treated with this thiopurine (36).…”
Section: Resultsmentioning
confidence: 99%
“…Multidrug resistance protein 4 (MRP4/ABCC4) belongs to the MRP family of drug transporters (20)(21)(22)(23) (21). Direct sequence analyses in our laboratory indicated that the allelic frequency of MRP4 G2269A was 14.7% in the Japanese population (24).…”
Section: Introductionmentioning
confidence: 88%
“…Recent studies have revealed that ABCC4 protects against thiopurine-induced hematopoietic toxicity by actively exporting thiopurine nucleotides (Krishnamurthy et al, 2008;Ban et al, 2010). ABCC4 is reportedly involved in the transport of antiviral agents, such as azidothymidine, adefovir, tenofovir, lamivudine, and ganciclovir (Shuetz et al, 1999;Adachi et al, 2002;Anderson et al, 2006;Imaoka et al, 2007), as well as anticancer drugs including 6-MP, 6-TG, methotrexate, and the camptothecins (Lee at al., 2000;Chen et al, 2002;Wielinga et al, 2002;Tian et al, 2005).…”
Section: Snp 2269g>a (Glu757lys) In Abcc4 Gene and Thiopurine Toxicitymentioning
confidence: 99%
“…Despite this situation, few data are available regarding the functions of these variants. Krishnamurthy et al have recently shown that patients carrying SNP 2269G>A (Glu757Lys) in the human ABCC4 gene have severely reduced ABCC4 function resulting from an impairment of its cell membrane localization (Krishnamurthy et al, 2008). ABCC4 protects against thiopurine-induced hematologic toxicity by actively exporting 6-TGN, a toxic metabolite in the thiopurine drug metabolic pathway.…”
Section: Snp 2269g>a (Glu757lys) In Abcc4 Gene and Thiopurine Toxicitymentioning
confidence: 99%